Kontribusi E-Puskesmas dan Integrasi Layanan Primer (ILP) terhadapInternal Service Quality dan Kepuasan Kerja di Puskesmas Tebet - Awwalunisa Aprilia Wijaya; Abdul Halik; Siti Mujanah (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Low patient satisfaction at Tebet Health Center reflects the need to improve Internal Service Quality (ISQ). Implementing e-Health Center and Primary Service Integration (ILP) has the potential to be a solution to improve ISQ, which ultimately impacts employee job satisfaction. This study used a quantitative cross-sectional design with a sample of 100 employees directly involved. Data were collected through structured questionnaires, semi-structured interviews, and observations. Instrument validity was tested with item-total correlation and reliability with cronbach’s alpha, meanwhile, data analysis used descriptive statistics and multiple linear regression. The research results reveal that partially, e-Health Center has a significant positive effect on ISQ (p-value = 0.000; t_{test}= 4.409) and ILP also has a significant positive effect on ISQ (p-value = 0.000$; ttest= 5.747$). Simultaneously, e-Health and ILP have a significant effect on ISQ (p-value = 0.000; Ftest = 31.108). Furthermore, it was found that the improvement of Internal Service Quality contributes positively and significantly to employee Job Satisfaction (p-value = 0.000; ttest= 4.780). The conclusion of this research confirms that e-Health and ILP are effective in improving ISQ, which directly implies an increase in employee job satisfaction at Tebet Health Center